Carreau Hybrid Nanofilm flow over a stretching sheet with suction/injection effect - Dian Adline Jalaluddin,; Roslinda Nazar,; Kohilavani Naganthran,; Ishak Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current work investigates the thin liquid film flow problem in the Carreau hybrid nanofilm (Al2O3-Cu/H2O) on a stretching sheet numerically. There is a suction/injection effect at the stretching sheet’s surface, which is permeable. The boundary value problem solver (bvp4c) in MATLAB is applied to solve the system of linear equations obtained from the partial differential equations by employing suitable similarity variables. The effect of suction was found to contribute to improving heat transfer performance. The suction parameters had a more significant impact on the skin friction coefficient and heat transfer rate than the injection parameters. It was determined that the diminution of the film thickness at the free surface and the improvement of convective heat transfer rates were the most significant effects of the injection.